Normal liver stiffness: A study in living donors with normal liver histology - Alsebaey, Ayman (World J Hepatol, 2015)
AIM: To define the normal range of liver stiffness (LS) values using transient elastography in living-related liver transplantation candidate donors with normal liver histology. METHODS: LS was measured using Fibroscan in 50 (16 women, 34 men) healthy potential donors (mean age 28.4 ± 5.9 years) who were being evaluated for liver donation for their relatives at the National Liver Institute, Menoufeya University, Egypt. All potential donors had normal liver tests and were negative for hepatitis B or C virus infection. Abdominal ultrasounds showed normal findings. None of the subjects had diabetes, hypertension, renal impairment, heart disease, or body mass index > 30 kg/m(2). All subjects had normal liver histology upon liver biopsy. They all donated the right lobe of their liver with successful outcomes. RESULTS: The mean LS was 4.3 ± 1.2 kPa (range: 1.8-7.1 kPa). The 5(th) and 95(th) percentiles of normal LS were 2.6 kPa and 6.8 kPa, respectively, with a median of 4 kPa; the interquartile range was 0.6 ± 0.4. LS measurements were not significantly different between men and women (4.4 ± 1.1 kPa vs 3.9 ± 1.3 kPa) and did not correlate with age. However, stiffness values were significantly lower in subjects with a body mass index < 26 kg/m(2) compared to those with an index ≥ 26 kg/m(2) (4.0 ± 1.1 kPa vs 4.6 ± 1.2 kPa; P <0.05). There were no differences in hospital stay or postoperative bilirubin, albumin,alanine and aspartate transaminases, or creatinine levels (at discharge) between donors with livers stiffness ≤ 4 kPa and those with stiffness > 4 kPa. CONCLUSION: Healthy donors with normal liver histology have a median LS of 4 kPa. Stiffness values are elevated relative to increase in body mass index.